Foreign policy implications for China’s “foreign-related ‘rule of law’” - Erie, MS (Elsevier, 2023)
In 2020, the Chinese Communist Party (CCP) launched the “foreign-related ‘rule of law” (FROL) reform, a reform that purports to modernize the intersection between Chinese domestic law and foreign and international law. Like many of China’s outward-facing initiatives, the FROL is more a loosely defined political discourse than a clear policy. Nonetheless, this article argues that the FROL may have implications for the role of Chinese law in China’s evolving foreign policy engagements. There are two overlapping contexts for the FROL: the first is purportedly defensive and reactive in nature and pertains to the US-China trade war and the exercise of lawfare in shaping that trade war. The second context is more assertive and proactive as the CCP proposes “Chinese-style modernization” for developing states around the world. Although Chinese-style modernization is more a creature of policy than formal law, law is becoming an important element in China’s approach. Against this backdrop, the FROL seeks to promote China’s definition of “rule of law” (fazhi) overseas and to integrate Chinese law into foreign and international law. Whereas the FROL marks a new stage in China’s legal development, its consequences for US-style rule of law and democratization are mixed. On the one hand, China explicitly proposes an alternative to that of the United States but, on the other hand, alarmist reactions need to be tempered by the empirical realities of China’s capacity deficiencies.